1999
DOI: 10.1063/1.124917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of channel doping on the low-frequency noise in GaN/AlGaN heterostructure field-effect transistors

Abstract: Low frequency noise in GaN/AlGaN heterostructure field effect transistors in non-ohmic region Low-frequency noise in AlGaN/GaN heterojunction field effect transistors on SiC and sapphire substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It is also not clear which model (the mobility fluctuation or the number fluctuation through random carrier trapping-detrapping) describes the 1/f noise in the GaN system the best. [10][11][12] It has been previously shown that GaN/AlGaN heterostructures have large piezoelectric coefficients which lead to strong electric polarization on (0001) faces of the wurtzite structures typically used to form GaN HFETs. [13][14] The latter results in appreciable charge densities, which are large enough to design HFETs without any channel doping.…”
Section: Introductionmentioning
confidence: 99%
“…It is also not clear which model (the mobility fluctuation or the number fluctuation through random carrier trapping-detrapping) describes the 1/f noise in the GaN system the best. [10][11][12] It has been previously shown that GaN/AlGaN heterostructures have large piezoelectric coefficients which lead to strong electric polarization on (0001) faces of the wurtzite structures typically used to form GaN HFETs. [13][14] The latter results in appreciable charge densities, which are large enough to design HFETs without any channel doping.…”
Section: Introductionmentioning
confidence: 99%
“…Special processing steps or device designs can lead to substantial reduction in the noise level. For example, it was shown that GaN/AlGaN heterostructure field-effect transistors (HFETs) where the high current density is achieved via increasing Al content in the barrier layer -the so-called "piezo-doping" -reveal lower 1/f noise level than GaN/AlGaN HFETs with conventional channel doping [46]. Several possible methods of 1/f noise reduction in graphene FETs have also been reported.…”
Section: Noise Reduction In Graphene Devicesmentioning
confidence: 99%
“…To compare with the experimental noise data, we included in Figure 4 the measured noise densities at different temperatures from AlGaN/AlN HFET reported in Ref. [30]. The data are normalized at certain low frequency values and shown as points in the figure.…”
Section: Resultsmentioning
confidence: 99%